Spiritual and religious perspectives in persons with visual impairment due to age-related macular degeneration - Carina Salzer; Lacramioara Samoila; Hosnasadat Mortazavi Moshkenani; Ovidiu Samoila (Frontiers in Psychology, 2023)
IntroductionAge-related macular degeneration (AMD) is one of the global leading causes of severe vision loss. Patients suffering from AMD face complex spiritual and mental challenges that have an impact on the course of their disease, their quality of life, and their relationship with their surroundings.MethodsA survey was carried out using a 21-item questionnaire between August 2020 and June 2021 among 117 patients from different countries to investigate how spirituality, religion, and their way of practicing them affected the experiences and daily lives of patients suffering from AMD, and whether it helped them cope with the disease.ResultsOur study concluded that spirituality and religion are important factors that facilitate patients’ ability to cope with a progressive degenerative disease such as AMD. Patients who are religious are more at peace with having AMD. Practices that contribute to patients being at peace in accepting the disease are regular prayers or meditation. Spirituality and religion are important components that promote a healthier and happier emotional state and mental wellbeing. In particular, by believing that death is not the end, patients feel more hopeful, which helps in their adjustment to a seemingly hopeless health condition. A significant number of AMD patients desire to talk about God with the medical staff. The profile of such patients could be those believing in a higher power, praying often, participating in religious services, being worried about the loss of vision, and needing assistance in daily life.DiscussionAn interdisciplinary and multidimensional team of medical health professionals including mental health workers and chaplains can be of great value in managing persons with AMD.